2007
DOI: 10.1103/physrevb.76.155423
|View full text |Cite
|
Sign up to set email alerts
|

Surface electronic structures of Ba overlayers on W(100), W(110), and W(111)

Abstract: The total energy distributions ͑TEDs͒ in field emission ͑FE͒ and photofield emission ͑PFE͒ and the work functions have been measured at room temperature for Ba adsorbed on W͑100͒, W͑110͒, and W͑111͒ in the range of coverage from 0 to 1 ML ͑monolayer͒. We observe two initial state peaks and three final state peaks on W͑100͒ / Ba, six initial state peaks and one final state peak on W͑110͒ / Ba, and two initial state peaks and two final state peaks on W͑111͒ / Ba. We extend the full-potential linear augmented pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…These two states, predominantly confined to the triplet of outermost W planes, have also been predicted (within a different theoretical approach and at slightly lower energies) by other authors, but never resolved experimentally as a double-peak feature before [7,18]. This indicates that our PFE measurements are in fact capable of revealing fine details of the surface DOS of the investigated sample.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These two states, predominantly confined to the triplet of outermost W planes, have also been predicted (within a different theoretical approach and at slightly lower energies) by other authors, but never resolved experimentally as a double-peak feature before [7,18]. This indicates that our PFE measurements are in fact capable of revealing fine details of the surface DOS of the investigated sample.…”
Section: Resultssupporting
confidence: 77%
“…Although this technique does not give any direct information on atomic positions, it is capable of revealing fine details of the electronic density of states (DOS) in the very surface region of the investigated sample (see, e.g., [4][5][6][7][8] and references therein). Thus, by contrasting the measured PFE spectra with the surface DOS distributions computed for various stable structural models, the latter can either be substantiated or invalidated.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the arrangement of Ba and O was Ba atop O adsorbed on W, with one Ba atom attached to one O atom in B-type cathodes and one Ba atom to two O atoms in M-type cathodes. Complementary computational work conducted by Ibrahim and Lee [93] also reported that the atomic arrangement of Ba on top of O adsorbed on W is more stable than O atop Ba and could yield work function close to those reported for dispenser cathodes.…”
Section: B-and M-type Cathodessupporting
confidence: 63%
“…This system can be used as a low-temperature thermionic cathode material [15]. It has been shown that Ba metal adsorbed on the (100), (110), and (111) faces of W results in a lowering of the work function and an increase in thermionic emission [16]. However, these surfaces are highly susceptible to oxidation and despite a slight increase in the work function of the system upon initial oxidation, the formation of a BaO film results in a further lowering of the work function.…”
Section: Introductionmentioning
confidence: 99%